PERANAN ZINC DAN VITAMIN E SEBAGAI ANTIOKSIDAN TERHADAP SEPSIS AKIBAT INFEKSI BAKTERI STAPHYLOCOCCUS AUREUS: SYSTEMATIC LITERATURE REVIEW - Napitupulu, Olivia Des Vinca Albahana; Rusip, Gusbakti; Mutia, Maya Sari (Poltekkes Kemenkes Bandung, 2025)
Sepsis caused by S. aureus infection is a serious condition requiring effective interventions to improve clinical prognosis. This study aimed to review the role of zinc and vitamin E as antioxidants in sepsis management through a systematic literature review (SLR) following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The research procedure consists of four main stages: identification, screening, eligibility, and inclusion, followed by qualitative data analysis. The review results showed that zinc and vitamin E significantly contribute to reducing NF-κB activation and inflammation, playing a crucial role in enhancing bacterial clearance and patient survival, particularly in neonates. Vitamin E functions as an antioxidant by preventing lipid peroxidation and increasing endogenous antioxidant levels such as glutathione and superoxide dismutase (SOD). Furthermore, vitamin E exhibits anti-inflammatory effects, as evidenced by the reduction of inflammatory biomarkers, including TNF-α and IL-6, which help protect vital organs such as the lungs and liver from inflammatory damage. Zinc, on the other hand, improves immune responses and reduces excessive inflammation, indicating that these two compounds can synergistically improve clinical outcomes in sepsis patients. This finding confirms that zinc and vitamin E supplementation has the potential to serve as an effective supportive strategy in reducing oxidative stress, modulating inflammation, and improving the prognosis of sepsis caused by Staphylococcus aureus.